The practitioner's handbook of team coaching - Clutterbuck, David; Gannon, Judie; Hayes, Sandra (Leadership expert); Iordanou, Ioanna; Lowe, Krister; MacKie, Doug (Routledge, 2019)
The world's challenges are becoming more and more complex and adapting to those challenges will increasingly come from teams of people innovating together. The Practitioner's Handbook of Team Coaching provides a dedicated and systematic guide to some of the most fundamental issues concerning the practice of team coaching. It seeks to enhance practice through illustrating and exploring an array of contextual issues and complexities entrenched in it. The aim of the volume is to provide a comprehensive overview of the field and, furthermore, to enhance the understanding and practice of team coaching. To do so, the editorial team presents, synthesizes and integrates relevant theories, research and practices that comprise and undergird team coaching. This book is, therefore, an invaluable specialist tool for team coaches of all levels; from novice to seasoned practitioners. With team coaching assuming an even more prominent place in institutional and organizational contexts nowadays, the book is bound to become an indispensable resource for any coaching training course, as well as a continuing professional development tool. This book is essential reading for anyone with an interest in coaching, in both practice and educational settings. It will be of use not only for professional coaches, but also for leaders, managers, HR professionals, learners and educators, in the business, public, independent and voluntary sectors.- Resumé vydavatel